Humor e política: na dinâmica das novas tecnologias da informação e comunicação - Martinho, Silvana Gobbi (2010)
The work aimed to study new forms of humor on the Internet, from the analysis of the site Charges.com during the year 2006. To develop the study, animations related to the theme of politics were selected, in which the main candidates for the presidential election were caricatured - Luiz Inacio Lula da Silva, Geraldo Alckmin and Heloisa Helena - or they were references. It was based on a quantitative and qualitative analysis aimed at identifying the main issues discussed and frameworks together with a description of the features of the animations. We conclude that the site has followed the logic of mass media, with a political agenda guided by the traditional media, holding a spectacle of contemporary society also at humor scope